LEVANTAMENTO DE COLEÃ“PTEROS EM PLANTIOS DE ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ spp. EM RONDONÃ“POLIS, ESTADO DE MATO GROSSO - Peres Filho, OtÃ¡vio; Dorval, Alberto; Siqueira, Samira Alvim; Berti Filho, Evoneo (REVISTA DE AGRICULTURA, 2020)
LEVANTAMENTO DE COLEÃ“PTEROS EM PLANTIOS DE ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ spp. EM RONDONÃ“POLIS, ESTADO DE MATO GROSSO